Attitudes of Policy Makers in Hawaii toward Public Health and Related Issues before and after an Economic Recession in the United States - Maddock, Jay E.; McGurk, Meghan; Lee, Thomas (Frontiers in Public Health, 2015)
Legislation and regulation at the state and local level can often have a greater impact on the public’s health than individual-based approaches. Elected and appointed officials have an essential role in protecting and improving public health. Despite this important role, little systematic research has been done to assess the relative importance of public health issues compared to other policy issues in times of economic hardship. This study assessed attitudes of elected and appointed decision makers in Hawaii in 2007 and 2013 to determine if priorities differed before and after the economic recession. Methods: Elected and appointed state and county officials were mailed surveys at both time points. Respondents rated the importance of 23 specified problems, of which 9 asked about specific public health issues. Results: The survey was completed by 126 (70.4%) respondents in 2007 and 117(60.9%) in 2013. Among the public health issues, five saw significant mean decreases. These variables included: climate change, pedestrian safety, government response to natural disasters, access to healthcare, and pandemic influenza. Obesity was the only public health issue to increase in importance across the two time points. In terms of relative ranking across the time points, only drug abuse and obesity were among the top ten priorities. Lack of public health training, pandemic influenza, and government response to natural disasters were among the bottom five priorities. Conclusions: After the economic recession, many public health issues have a lower priority among Hawaii’s policy makers than before the downturn. Additional education and advocacy is needed to keep public health issues on the minds of decision makers during tough economic times.